The Abidjan-Ouagadougou Railway Concession - Budin, Karim-Jacques; Mitchell, Brigitta (World Bank, Washington, DC, 2012)
Since the 1980s, most Sub-Saharan African railways have been experiencing a severe crisis: declining traffic and revenue, lack of market orientation and poor service, continued operation of high-loss passenger services, poor maintenance, gross overstaffing, lack of technical and financial discipline, and heavy financial losses. Attempts to 'restructure' railways as public entities have generally failed. Involvement of the private sector in railway operations under a concession arrangement now seems to be a promising tool for transforming railways into business-oriented enterprises. The concession technique, successfully applied in Latin America, was used for the first time in Sub-Saharan Africa in Cote d'Ivoire and Burkina, who jointly concessioned the Abidjan-Ouagadougou railway to a private operator in December 1994.